2011
DOI: 10.1073/pnas.1109490108
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative ratiometric discrimination between noncancerous and cancerous prostate cells based on neuropilin-1 overexpression

Abstract: A multiplexed, ratiometric method is described that can confidently distinguish between cancerous and noncancerous epithelial prostate cells in vitro. The technique is based on bright surfaceenhanced resonance Raman scattering (SERRS) biotags (SBTs) infused with unique Raman reporter molecules, and carrying cellspecific peptides. Two sets of SBTs were used. One targets the neuropilin-1 (NRP-1) receptors of cancer cells through the RPARPAR peptide. The other functions as a positive control (PC) and binds to bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 31 publications
1
67
0
Order By: Relevance
“…In fact, it has been demonstrated that SEPs can adhere to tumor tissues in less than minutes, although the nonspecifically adsorbed SEPs must be removed by washing the tissue with serum (Wang et al 2014a). The obstacle set by the high background distribution of non-specifically bound nanoparticles can be overcome by implementing ratiometric approaches where one of the SEP type in the particle cocktail is used as a nonspecific internal reference to visually enhance the preferential adhesion of other targeting nanoparticles on tumor tissues (Mallia et al 2015;Oseledchyk et al 2017;Pallaoro et al 2011). Implementation of these methods is rather straightforward for SERS imaging due to the high degree of multiplexing provided by the narrow Raman linewidths.…”
Section: Sep Characterization Of Tumor Tissuesmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, it has been demonstrated that SEPs can adhere to tumor tissues in less than minutes, although the nonspecifically adsorbed SEPs must be removed by washing the tissue with serum (Wang et al 2014a). The obstacle set by the high background distribution of non-specifically bound nanoparticles can be overcome by implementing ratiometric approaches where one of the SEP type in the particle cocktail is used as a nonspecific internal reference to visually enhance the preferential adhesion of other targeting nanoparticles on tumor tissues (Mallia et al 2015;Oseledchyk et al 2017;Pallaoro et al 2011). Implementation of these methods is rather straightforward for SERS imaging due to the high degree of multiplexing provided by the narrow Raman linewidths.…”
Section: Sep Characterization Of Tumor Tissuesmentioning
confidence: 99%
“…The outer protective layer improves nanoparticle stability and prevents the desorption of the SERS codes from the particle surface. Further, the external stabilizing coating provides functional groups on their surface for further bioconjugation (e.g., antibodies or aptamers) for selective targeting Conde et al 2014;Pallaoro et al 2011).…”
Section: Surface-enhanced Raman Scattering Encoded Particlesmentioning
confidence: 99%
“…Many of the strategies that have been developed to date use SERS substrates that contain a peptide or protein to target a specific cellular marker, often on the cell membrane, that is unique to cancer cells or has a differential expression in cancerous cells. 521,[548][549][550][551][552] Moskovits and coworkers developed one such strategy for distinguishing cancerous epithelium prostate cells from non-cancerous cells. 549 Their approach was to ratio the signal obtained from two separate Ag nanoparticle based SERS substrates to detect the over expression of neuropilin-1 in the cancerous cell line.…”
Section: Detection Of Cancer Cells and Treatment Efficacymentioning
confidence: 99%
“…Ag NPs have the most intensive plasmon absorption, 5 can be promising as a disinfecting addition in form of NPs' colloidal solutions, [6][7][8] can be used for the long-term control of the processes in cells of live organisms or as biomarkers in cancer diagnosis methods. 9 Chemical methods of NPs' synthesis (especially metallic ones) are well-known, [10][11][12] but, apart from NPs obtained as a result of reduction reactions or ion exchange, there are always by-products present, which confines the use of these methods. That is why lately in the last 10 years new alternative ways of getting metal NPs are being developed, in particular with the use of laser irradiation.…”
Section: Introductionmentioning
confidence: 99%